2016
DOI: 10.5303/jkas.2016.49.1.25
|View full text |Cite
|
Sign up to set email alerts
|

THE INFRARED MEDIUM-DEEP SURVEY. V. A NEW SELECTION STRATEGY FOR QUASARS AT z > 5 BASED ON MEDIUM-BAND OBSERVATIONS WITH SQUEAN

Abstract: We present our first results of the survey for high redshift quasars at 5 z 5.7. The search for quasars in this redshift range has been known to be challenging due to limitations of filter sets used in previous studies. We conducted a quasar survey for two specific redshift ranges, 4.60 ≤ z ≤ 5.40 and 5.50 ≤ z ≤ 6.05, using multi-wavelength data that include observations using custom-designed filters, is and iz. Using these filters and a new selection technique, we were able to reduce the fraction of interlope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 49 publications
(59 reference statements)
2
21
0
Order By: Relevance
“…While the 70 candidates for z ∼ 5 quasar are shown as the gray histogram, the total 58 candidates with m725-and m775-band observations are given in the blue histogram, and 45 of them also have m675-band photometry (the green histogram). Among the mediumband observed candidates, 33 candidates satisfy the mediumband color criteria given by Jeon et al (2016) (the orange histogram), and 28 of them were spectroscopically identified as high redshift quasars by this work and previous works (M18; Ikeda et al 2017). Note that the 28 candidates are given in the red hatched histogram for easy distinction from the orange histogram.…”
Section: Medium-band Color Selection and Its Efficiencysupporting
confidence: 63%
See 4 more Smart Citations
“…While the 70 candidates for z ∼ 5 quasar are shown as the gray histogram, the total 58 candidates with m725-and m775-band observations are given in the blue histogram, and 45 of them also have m675-band photometry (the green histogram). Among the mediumband observed candidates, 33 candidates satisfy the mediumband color criteria given by Jeon et al (2016) (the orange histogram), and 28 of them were spectroscopically identified as high redshift quasars by this work and previous works (M18; Ikeda et al 2017). Note that the 28 candidates are given in the red hatched histogram for easy distinction from the orange histogram.…”
Section: Medium-band Color Selection and Its Efficiencysupporting
confidence: 63%
“…The candidates satisfying the criteria were visually inspected to exclude spurious objects such as cross-talks, (Gunn & Stryker 1983) and dwarf (Burrows et al 2006). The dotted lines are the medium-band selection criteria provided by Jeon et al (2016), while the dashed lines are the additional criteria presented in this work.…”
Section: Broad-band Color Selectionmentioning
confidence: 99%
See 3 more Smart Citations